Clinical results and perinatal outcome in PGT-A cycles with trophectoderm biopsy: a 4-year follow up study. (April 2019) - Buendía, Pilar; Escrich, Laura; Beltrán, Diana; Delgado, Arantxa; Tejera, Alberto; Insúa, Fernanda; Castelló, Damià; Mifsud, Amparo; Santos, María José de Los; Mercader, Amparo
Abstract : Introduction: Trophectoderm biopsy is one of the strategies to obtain a sample to analyze the aneuploidies of the embryo. Blastocyst vitrification after biopsy give us more time for analysis. Moreover, it is a strategy that allows transfer back the normal embryo in a non-stimulated cycle. The endpoint of an assisted reproduction cycle is a healthy live newborn at home. Therefore, perinatal outcome follow-up is necessary. The objective of this study was to assess the results and perinatal outcome obtained in couples from our PGT-A program with trophectoderm biopsy. Material & Methods: Retrospective collection data value (1503-VLC-017-AM) from our PGT-A program (2014-2017) and pregnancies and perinatal follow-up resulted from these cycles until September 2017. This study included 1, 818 PGT-A cycles (39 in 2014, 98 in 2015, 693 in 2016 and 1, 051 in 2017). Indications for PGT-A were advanced maternal age (64.8%), repetitive implantation failure (12.5%), recurrent miscarriage (7.2%), severe male factor (10.7%), previous pregnancy with aneuploidy (2.5%) and mixed causes (2.3%). Trophectoderm biopsy was carried out in fresh blastocysts. Biopsies were performed on day-5 or day-6 and one hour after biopsy blastocysts were vitrified until results. Analysis by NGS were performed. Only euploid blastocysts were transferred in a next cryotransfer. Data regarding to deliveries and babies were obtained from the medical records, as well as the reports sent by the referral center and from the survey sent to the patients. Results: For cycles with almost one euploid blastocyst, the corresponding rates were 87.2% (n=39) in 2014, 71.4% (n=98) in 2015, 77.9% (n=693) in 2016 and 65.2% (n=1051) in 2017. Number of transferences were: 70 in 2014, 109 in 2015, 613 in 2016 and 695 in 2017. Known implantation rate and ongoing pregnancy were 64.9% and 48.9%, respectively. Number of double embryo transfer (DET) were high in 2014 (60.8%) and in 2015 (47.7%), and the multiple pregnancies remained high too (51.0%). Because the ongoing pregnancy rate in this years the transfer policy changed from DET to single embryo transfer (SET). In 2016 and 2017, SET represented 71.0% and 78.9% from the embryo transfers performed, respectively, decreasing the multiple pregnancy rates to 16.1%. Caesarean section was performed in 63.8% of the deliveries reported. Out of 336 children reported born, sex distribution was: 53.5% males and 46.5 females. Very premature delivery (before week 32) occurred in 2.5% of the pregnancies. A total of 336 babies were born. The average weigth was 3240±1200g and the average length was 50.1±4.9cm. Several congenital abnormalities were found that were not related to the PGT indication (less than 1%). Conclusion: Our results suggest than trophectoderm biopsy is a safe option that does not compromise the clinical results and perinatal outcome in a PGT-A program. The annual data collection provide an important resource for data mining and for following trends in PGT practice, the same way ESHRE Consortium and ASRM recommend.